Validation of the PEACE score for predicting abnormal echocardiographic findings in pulmonary embolism patients - Kazım Ersin Altınsoy (BMC Emergency Medicine)
Abstract Background Pulmonary embolism (PE) is a life-threatening condition requiring rapid risk stratification for optimal management. The Pulmonary Embolism Advanced Cardiac Evaluation (PEACE) Score is a novel tool integrating clinical, laboratory, and echocardiographic parameters to assess disease severity. This study aimed to evaluate the correlation between PEACE Score and echocardiographic abnormalities in PE patients, and to determine its effectiveness as a rapid risk assessment tool in emergency settings. Methods Between June 2020 and June 2024, 120 patients were prospectively screened and enrolled in the study after being diagnosed with pulmonary embolism via CT angiography in the emergency department. Patients were categorized into three groups according to PEACE score as low risk (< 3 points, n = 42), intermediate risk (3–5 points, n = 52) and high risk (> 5 points, n = 26). Echocardiographic findings were not used for stratification but rather analyzed as outcome variables to assess the discriminative validity of the PEACE Score. Demographic data, laboratory findings and echocardiographic parameters were recorded. Patients were followed up for at least 1 year. Follow-up from 3 months to 6 months was evaluated and mortality rates at the end of 1 year were determined. Results PEACE Score was strongly correlated with echocardiographic abnormalities (r = 0.685, p < 0.001) and inflammatory markers, including CRP (r = 0.524, p < 0.001). The PEACE Score had the highest diagnostic value for predicting echocardiographic abnormalities, with an AUC of 0.82 (95% CI: 0.74–0.90, p < 0.001). Specifically, in predicting right ventricular dysfunction, the PEACE Score achieved an AUC of 0.85 (95% CI: 0.77–0.93, p < 0.001). A cutoff of > 5 points showed a sensitivity of 84.6% and specificity of 79.2% for detecting severe echocardiographic abnormalities. One-year survival rates were 45% in the high-risk group, 65% in the intermediate-risk group, and 85% in the low-risk group. Kaplan-Meier analysis confirmed significant differences in survival among risk groups (p < 0.001). Conclusion The PEACE Score demonstrated a strong association with echocardiographic abnormalities and patient survival in emergency department PE cases. These findings suggest that PEACE may serve as a valuable tool for rapid risk stratification, aiding emergency physicians in early clinical decision-making. Specifically, high PEACE Scores were associated with a greater need for thrombolytic therapy and ICU admission, suggesting its potential utility in guiding treatment escalation and resource allocation in critically ill PE patients. Clinical trial number Not applicable.